Pure Contagion and Investors Shifting Risk Appetite : Analytical Issues and Empirical Evidence - Kumar, Manmohan (IMF Working Papers; Working Paper ;, 2001)
This paper discusses a "pure" form of financial contagion, unrelated to economic fundamentals - investors' shifting appetite for risk. It provides an analytical framework for identifying changes in investors' risk appetite and discusses whether it is possible to directly measure them in a way that can enable policy makers to differentiate between financial contagion and domestic fundamentals as the immediate source of a crisis. Daily measures of risk appetite are computed and their usefulness in predicting financial crises is assessed.